A Study About Repetition of Group of Data and Avoid the Problem - Rosy, M Angelin; Sangeetha, K; Muthu, M. Felix Xavier (International Journal of Computer Sciences and Engineering, 2025)
Technology is improving day by day, to manage technology by time and trend. To share data in many ways, such as share it, whatsapp, facebook hike and Twitter By using these apps, sharing and storing the data is easy. Technology is improved by innovation and renovation. Cloud is used to store the big data. Users share information through multiple group members in the cloud with low maintenance and costs. Data owner is not able to control over their data. Various techniques are used to support user privacy and data sharing. The use of the mobile devices in cloud computing environment to various kinds of attacks like, unauthorized access. This paper introduces on how to avoid the repetition of data using normalization forms.